2018
DOI: 10.15419/bmrat.v5i9.474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasmodium falciparum K13 gene polymorphism and susceptibility to dihydroartemisinin in an endemic area

Abstract: Introduction: Plasmodium falciparum has developed resistance to artemisinin drugs in Southeast Asia, and its reduced sensitivity has been reported in other regions. This study aims to determine parasite susceptibility to the bioactive form of artemisinin derivatives- dihydroartemisinin (DHA)-, and to detect the K13 polymorphism in isolates from an endemic area of Nigeria. Methods: Ex-vivo response in 55 parasites isolates obtained from malaria-positive patients were exposed to pulse DHA concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…None of them was among the ten SNPs (F446I, N458Y, M476I, Y493H, R539T, I543T, P553L, R561H, P574L and C580Y) which have been validated to be associated with artemisinin resistance in Southeast Asia, South America and Rwanda [ 2 , 6 9 ]. The absence of the validated mutations in our study is in line with many recent studies carried out in Africa [ 32 40 ] and in Nigeria [ 20 , 27 , 29 , 34 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…None of them was among the ten SNPs (F446I, N458Y, M476I, Y493H, R539T, I543T, P553L, R561H, P574L and C580Y) which have been validated to be associated with artemisinin resistance in Southeast Asia, South America and Rwanda [ 2 , 6 9 ]. The absence of the validated mutations in our study is in line with many recent studies carried out in Africa [ 32 40 ] and in Nigeria [ 20 , 27 , 29 , 34 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since, a handful of studies have documented treatment failure in patients treated with artemether and/or ACT partner drugs like amodiaquine, e.g., [ 13 , 15 , 16 , 17 ]. Studies carried out to detect mutations in the kelch13 gene to date have found none of the major mutations associated with delayed parasite clearance in isolates from Nigeria [ 18 , 19 , 20 , 21 , 22 ]. However, except for [ 22 ] these recent studies were all carried out in southern Nigeria, with little known of kelch13 resistance markers in northern Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, studies in the absence of Kelch13 -resistant genotypes in P. falciparum isolates from malaria patients in Cameroon were associated with total parasite clearance, high reduction of parasite loads, and resolved symptoms [ 22 ]. Other studies concerning polymorphism have reported that genetic variations in the Pfmdr1 and Pfcrt genes are associated with reduced susceptibility to aminoquinoline antimalarial drugs, especially when compared to parasites that have not been exposed [ 23 ]. In addition, a study reported the prevalence of polymorphisms in the Pfkelch13, Pfcrt , and Pfmdr1 genes among Chinese migrant workers who returned to Guangxi Province from Africa.…”
Section: Introductionmentioning
confidence: 99%